2015
DOI: 10.1017/jfm.2015.410
|View full text |Cite
|
Sign up to set email alerts
|

Universal statistics of point vortex turbulence

Abstract: A new methodology, based on the central limit theorem, is applied to describe the statistical mechanics of two-dimensional point vortex motion in a bounded container D, as the number of vortices N tends to infinity. The key to the approach is the identification of the normal modes of the system with the eigenfunction solutions of the so-called hydro- The pdf of the leading vorticity projection is of particular interest because it has a unimodal distribution at low energy and a bimodal distribution at high ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 45 publications
(53 reference statements)
1
28
0
Order By: Relevance
“…This efficiently injects many vortices into the BEC with minimal sound excitation [27,28]. We find the vortices rapidly organise into two Onsager vortex clusters that settle on the major axis [29] and are visible following a short 3 ms time-of-flight expansion ( Fig. 2B).…”
mentioning
confidence: 87%
“…This efficiently injects many vortices into the BEC with minimal sound excitation [27,28]. We find the vortices rapidly organise into two Onsager vortex clusters that settle on the major axis [29] and are visible following a short 3 ms time-of-flight expansion ( Fig. 2B).…”
mentioning
confidence: 87%
“…The phenomenon stems from the bounded phase space, which supports negative temperature states that favor the spontaneous clustering of like-sign vortices. As an equilibrium statistical mechanics problem, cluster formation in 2D vortex systems has attracted much attention [5,[10][11][12][13][14][15][16][17][18][19][20]. Building on Joyce and Montgomery's formulation of vortex statistical mechanics [10], Smith and O'Neil [17,18] investigated the single-charge 2D plasma using the point-vortex model in a rotating container and showed that the formation of a nonaxisymmetric cluster resembles a second-order phase transition.…”
Section: Introductionmentioning
confidence: 99%
“…6] induced by the point vortices raises no problem when used as the singularity distribution on the domain boundaries and/or as the circulation carrier at each timestep. However, Esler and Ashbee [16], and Kuvshinov and Schep [21] showed, in their work on point vortices to realize a white noise signal, that there exists a problem when approximating the vorticity with delta functions (point vortices), i.e., infinite spikes, which is an associated singularity in the streamfunction and velocity field. This singularity appears when the distance to the point vortex becomes very small, |r − r | → 0: both streamfunction and velocity become very large; the first blows up logarithmically fast and the other like r −1 .…”
Section: B Point Vortex Singularity and Gaussian Wave Shape Vorticesmentioning
confidence: 99%
“…Chapman [13], Benzi [14], and Elhmaidi [15] used a similar method to realize a two-dimensional synthetic turbulent inflow using point vortices. Esler [16] studied the behavior of a finite number of point vortices and examined the possibility of replacing a turbulent flow with a collection of point vortices. However, there is a problem with approximating the vorticity with point vortices (delta functions), i.e., infinite spikes, which introduces an associated singularity in the streamfunction and velocity fields.…”
Section: Introductionmentioning
confidence: 99%